2021
DOI: 10.1002/cpt.2385
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of High‐Volume Subcutaneous Crenezumab, With and Without Recombinant Human Hyaluronidase in Healthy Volunteers

Abstract: Compared with intravenous formulations, subcutaneous (s.c.) formulations of therapeutic monoclonal antibodies may provide increased patient access and more convenient administration options, although historically highvolume s.c. administration (> 10-15 mL) has been challenging. We report results from two phase I studies in healthy participants (GP29523 and GP40201) that evaluated s.c. crenezumab, an anti-Aβ monoclonal antibody in development for individuals at risk for autosomal-dominant Alzheimer's disease. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In two phase I studies including healthy participants, it was proved that crenezumab was well-tolerated in healthy participants with an acceptable safety profile ( Dolton et al, 2021 ). However, phase 3 clinical trials recruited 750 patients with prodromal to mild AD, and the outcomes were completely negative, since there was no difference between crenezumab and placebo subgroups or within the prodromal vs. mild AD subgroups assessed by several parameters, such as Alzheimer’s Disease Assessment Scale–Cognitive Subscale score (ADAS-Cog) and MMSE ( Salloway et al, 2018 ), suggesting that crenezumab had no therapeutic effect on AD symptoms.…”
Section: Immunotherapies With Mabs In Patients With Ad and Its Animal...mentioning
confidence: 99%
“…In two phase I studies including healthy participants, it was proved that crenezumab was well-tolerated in healthy participants with an acceptable safety profile ( Dolton et al, 2021 ). However, phase 3 clinical trials recruited 750 patients with prodromal to mild AD, and the outcomes were completely negative, since there was no difference between crenezumab and placebo subgroups or within the prodromal vs. mild AD subgroups assessed by several parameters, such as Alzheimer’s Disease Assessment Scale–Cognitive Subscale score (ADAS-Cog) and MMSE ( Salloway et al, 2018 ), suggesting that crenezumab had no therapeutic effect on AD symptoms.…”
Section: Immunotherapies With Mabs In Patients With Ad and Its Animal...mentioning
confidence: 99%
“… 94 Amivantamab with hyaluronidase Unavailable Unknown An ongoing Phase 1b dose-escalation study with 81 patients with various advanced solid tumors found that SC amivantamab 1600 mg (or 2240 mg in patients weighing ≥80 kg) administered every other week had similar exposure to the approved IV dose (1050 mg every other week, or 1400 mg in patients weighing ≥80 kg); resulted in lower C max and equal or higher C trough and AUC 0-336 h ; and was associated with a lower incidence of infusion-related reactions and related symptoms. 13 Crenezumab with hyaluronidase 66% 96 No A Phase 1 study with 72 adult participants receiving SC crenezumab at different combinations of dose (1,700–6,800 mg), flow rate (2–4 mL/minute), and infusion volume (10–40 mL) and with and without co-formulation with hyaluronidase found that hyaluronidase decreased infusion site swelling incidence but was associated with larger areas of infusion site erythema, and co-formulation with hyaluronidase did not significantly affect patient pain, dose proportionality, bioavailability, drug half-life, or systemic exposure. 96 VYVGART HYTRULO® (efgartigimod with hyaluronidase) ~50% 97 Unknown VYVGART HYTRULO® has comparable half-life to that of IV administration but is associated with more injection site reactions (reported in 21 of 55 patients, or 38%), including rash, skin redness, itching, bruising, pain, and hives.…”
Section: Subcutaneous Delivery Product Development Considerationsmentioning
confidence: 99%
“…SC PK data from these programs, as well as several other antibodies in clinical development with rHuPH20, were leveraged in this work. [10][11][12][13][14][15][16][17][18] Other drug modalities commercialized with rHuPH20, that is, polyclonal IgG…”
Section: Introductionmentioning
confidence: 99%
“…rHuPH20 is approved in several commercial SC products, five of which are monoclonal antibodies: daratumumab (Darzalex FASPRO®/DARZALEX® SC), trastuzumab (Herceptin Hylecta™/Herceptin® SC), pertuzumab/trastuzumab (Phesgo®), and rituximab (Rituxan Hycela®/MabThera®) in the United States, and atezolizumab (Tecentriq® SC) in Great Britain. SC PK data from these programs, as well as several other antibodies in clinical development with rHuPH20, were leveraged in this work 10–18 . Other drug modalities commercialized with rHuPH20, that is, polyclonal IgG (HyQvia®) and efgartigimod alfa (antibody fragment) (VYVGART® HYTRULO), were not included in the analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation